Trophic ecology of squids in the Benguela Upwelling System assessed through stomach content, fatty acid and stable isotopes analyses in austral spring 2021 - Stomach contents of squids - Kira Izabela Kremer; Daniel Oesterwind; Anne F Sell (PANGAEA, 2025)
Squids were collected during the research cruise SO285 on RV Sonne in the northern (nBUS) and southern (sBUS) Benguela Upwelling System between September 13 and October 8, 2021 in order to determine their trophic position and nutritional ecology. The cruise was part of the TRAFFIC (Trophic tRAnsfer eFFICiency in the Benguela Current) project. Samples were retrieved from rectangular midwater trawl (RMT) net hauls at 8 stations in the nBUS (sampling ranged from surface down to 230–600 m) and 5 stations in the sBUS (sampling ranged from surface down to 500–750 m). Furthermore, some squids were caught using hook and line in the upper two meters of the water column at 2 stations in the nBUS (ranging from 20 to 115 min per station, 4–5 rods) and 4 stations in the sBUS (ranging from 45 to 105 min per station, 4–6 rods). At 1 station in sBUS one squid was retrieved from a neuston catamaran haul (NCAT) used to sample the surface layer (0–20 cm sampling depth). Dorsal mantle length (DML) of each specimen was measured to the nearest mm below. Visual stomach content analyses of 53 stomachs from chosen epi- and mesopelagic squid species were performed using a stereo-microscope (7.5–50x magnification). Stomach content analyses showed that squid species preyed on a variety of organisms ranging from crustaceans to lanternfishes (Myctophidae) and flying squids (Ommastrephidae).